The Role of Index and Ring Fingers in Gender Identification and Height Estimation - Akhlaghi, Mitra; Sheikhazadi, Ardeshir; Khazaie, Fatemeh; Rafiee, Shima; Sadeghian, Mohammad Hossein (International Journal of Medical Toxicology and Forensic Medicine, 2019)
Background: It is a challenge in forensic medicine to identify deceased bodies when body dismembered from remaining body parts, such as hands, arms, and feet. We aimed to determine gender and the correlation between stature, and index and ring fingers in an Iranian population. Methods: In this cross-sectional study, 200 Iranian students aged between 18 and 25 years were included (2016-2017). The length of the nondominant index and ring fingers were measured from proximal crease to the tip. The exclusion criteria were a history of heavy physical work by hand, hand vocational sports, anatomical musculoskeletal deformities, and chronic internal diseases (diabetes, thyroid disorders, renal failure, etc.). The obtained data were analyzed using SPSS. t-test, Pearson’s correlation coefficient, and correlation and regression models were used to analyze the achieved data. Results: The mean height was 179 cm in males and 164 cm in females. The mean index and ring fingers lengths were 73 mm and 74 mm in males, and 68 mm and 68 mm in females, respectively. The mean sum of index and ring fingers lengths were 147 mm in males and 136 mm in females. Height, index and ring fingers length, and the sum of them significantly differed between genders (P<0.0001). The accuracy of gender determination was 92%, 71%, 73% and 74.5% in terms of stature, index finger length, ring finger length, and the sum of index and ring fingers length, respectively. The correlation between height and index finger length, as well as the height and ring finger length, were significant in males, females, and total cases (P<0.0001). Conclusion: Based on this study, index and ring fingers lengths can be used to predict height and determine gender.